Efficacy and tolerability of adjunctive lacosamide in pediatric patients with focal seizures. (17th September 2019) - Farkas, Viktor; Steinborn, Barbara; Flamini, J. Robert; Zhang, Ying; Yuen, Nancy; Borghs, Simon; Bozorg, Ali; Daniels, Tony; Martin, Paul; Carney, Hannah C.; Dimova, Svetlana; Scheffer, Ingrid E.
Abstract : Objective: To evaluate efficacy and tolerability of adjunctive lacosamide in children and adolescents with uncontrolled focal (partial-onset) seizures. Methods: In this double-blind trial (SP0969; NCT01921205), patients (age ≥4–<17 years) with uncontrolled focal seizures were randomized (1:1) to adjunctive lacosamide/placebo. After a 6-week titration, patients who reached the target dose range for their weight (<30 kg: 8–12 mg/kg/d oral solution; ≥30–<50 kg: 6–8 mg/kg/d oral solution; ≥50 kg: 300–400 mg/d tablets) entered a 10-week maintenance period. The primary outcome was change in focal seizure frequency per 28 days from baseline to maintenance. Results: Three hundred forty-three patients were randomized; 306 (lacosamide 152 of 171 [88.9%]; placebo 154 of 172 [89.5%]) completed treatment (titration and maintenance). Adverse events (AEs) were the most common reasons for discontinuation during treatment (lacosamide 4.1%; placebo 5.8%). From baseline to maintenance, percent reduction in focal seizure frequency per 28 days for lacosamide (n = 170) vs placebo (n = 168) was 31.7% ( p = 0.0003). During maintenance, median percent reduction in focal seizure frequency per 28 days was 51.7% for lacosamide and 21.7% for placebo. Fifty percent responder rates (≥50% reduction) were 52.9% and 33.3% (odds ratio 2.17, p = 0.0006). During treatment, treatment-emergent AEs were reported by 67.8% lacosamide-treated patients (placebo 58.1%), most commonly (≥10%) somnolence (14.0%, placebo 5.2%) and dizziness (10.5%, placebo 3.5%). Conclusions: Adjunctive lacosamide was efficacious in reducing seizure frequency and generally well tolerated in patients (age ≥4–<17 years) with focal seizures. ClinicalTrials.gov identifier: NCT01921205. Classification of evidence: This trial provides Class I evidence that for children and adolescents with uncontrolled focal seizures, adjunctive lacosamide reduces seizure frequency.